"Spiritually Dynamic but Ecclesially Deviant": African Immigrant Christianity and New Ecumenical Terrain in the West. (April 2023) - Krabill, Matthew J.
This article argues that the presence of African immigrant Christianity in the West presents a critical, yet largely overlooked and unexplored arena for exploring ecumenical relations. The article draws on research among African immigrant Mennonites in the US and contends that their presence in homegrown Mennonite spaces poses unprecedented challenges and opportunities to the potential for shared ecclesial life. The article identifies and assesses several key challenges and areas of misalignment and argues that from the African immigrant perspective, the encounter with homegrown Christianity proves to be one of its formidable and intractable ecclesial challenges.